Growth Trend and Migration of Rural Population: a Case Study in Damavand, Iran - Taj, Shohreh; Arzjani, Zahra; Latifeh, Nahid (International Journal of Bio-resource and Stress Management, 2023)
Population dynamics has direct relationship with natural resource management of the area. The study was conducted in Damavand area of Tehran province which is located in the East Province of Iran to find out the growth and stability of rural populations in the selected villages on six villages namely; Aro, Hvyr, Dhnar,Mumj, Khosro and Ayne varzan during 1996 and 2006. During 1996, highest (1035) population was observed in Aro village followed by Ayne varzan (638) and Hvyr (267) with the least (55) population in Dhanar irrespective of age groups, whereas in 2006, highest population was counted in Aro village whereas lowest in Dhanar village. Estimated data for 2011 revealed a variation in the population dynamics. Decadal data represented that Hvyr population had shown negative growth over 10 years which was exceptional than any other villages. This indicated the clear trend of population in migrating from village to village or town in search of jobs all around. Government should take initiatives in creating jobs opportunities like soil and water management practices that may encour¬age villagers and job opportunities as well.